One-Dimensional (1D) River Analysis of a River Basin in Southern Luzon Island in the Philippines Using Lidar Digital Elevation Model - J. Tan, Fibor; Jade R. Rarugal, Edgardo; Aldrine A. Uy, Francis (International Journal of Engineering and Technology, 2018)
Flooding is a perennial problem in the Philippines during the monsoon season intensified by the effects of typhoon. On average, there are 20 typhoons that enter the Philippine Area of Responsibility (PAR), and many of these make landfall causing catastrophic aftermath. Extreme rainfall events could lead to flooding in the downstream floodplain and landslide in mountainous terrains. In this study, which is for the case of Calumpang River that drains to the populated and developing region of Batangas City, the focus is on flooding in the floodplain areas. The river was modelled using LiDAR digital elevation model (DEM) that has an accuracy of 20cm in the vertical and 50cm in the horizontal. The result of this is river hydraulic model that can be used to accurately generate flood inundation simulations and flood hazard maps.Â Â